Pengembangan Game Edukasi Berbasis Android dengan Articulate Storyline Pada Materi Sistem Koordinat - Ulum, Qoidatul; Manoy, Janet Trineke; Fiangga, Shofan (MATHEdunesa, 2024)
There are still many learners who have difficulty in coordinate system material. Efforts to overcome the difficulties of students in mathematics lessons coordinate system material, one of which is the use of learning media. One of the media that can be used in learning in the current era is interactive learning media. However, there are many obstacles experienced by teachers in making interactive learning media. Currently, interactive learning media is needed that allows students to learn material that can be accessed by students anywhere independently and without teacher assistance. Educational games can be developed in the form of applications that run using smartphones to make them more practical and easy to use by students. But more students use smartphones just for fun, such as playing games that have nothing to do with learning. In order for a smartphone to be used, an operating system such as Android is needed. Based on the description above, a new and easy to work Android-based educational game is needed, so researchers chose Articulate Storyline software to create an Android-based educational game. Related to what has been described above, researchers developed an Android-based educational game with Articulate Storyline on the Coordinate System material. This study aims to describe the process of developing Android-based educational games with Articulate Storyline on Coordinate System material and describe the results of developing Android-based educational games with Articulate Storyline on valid, practical, and effective Coordinate System material. The method used in this research is development research (Reasearch and Development). The development model used in this research is the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. Validity instruments in the form of validation questionnaires, practical instruments in the form of student response questionnaires, and effectiveness instruments carried out pre-test and post-test. This Android-based educational game is implemented for students of grade VIII J SMPN 26 Surabaya. The results showed that, this educational game obtained a validity percentage value of 90.25% so that it can be categorized as very valid. Educational games are said to be practical because the results obtained from the student response questionnaire obtain a percentage value 89,425 % so it is categorized as very practical. The results of using this educational game are also effective because the N-gain results obtained are 0.92505847 which is in the high category.